Vacuum electrospray deposition for face-on orientation and interface preservation in organic photovoltaics - Lee, Younjoo; Jeong, Junkyeong; Jung, Kwanwook; Lee, Jeihyun; Youn, Yungsik; Park, Soo hyung; Lee, Hyunbok; Yi, Yeonjin (Nature Publishing Group, 2025)
Despite recent advancements in organic photovoltaics (OPVs), further improvements in power conversion efficiency (PCE) and device lifetime are necessary for commercial viability. Strategies such as optimizing the molecular orientation and minimizing the charge traps of organic films are particularly effective in enhancing photovoltaic performance. In this study, we successfully utilized vacuum electrospray deposition (VESD) to achieve favourable face-on stacking geometries while preserving the integrity of the interfaces in poly(3-hexylthiophene-2,5-diyl) (P3HT): [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) bulk heterojunction (BHJ) films. Unlike conventional spin-coated (SC) P3HT: PCBM BHJ films, which predominantly exhibit an edge-on orientation, VESD facilitates a beneficial face-on orientation, improving vertical charge transport through enhanced π-π stacking interactions. Furthermore, VESD effectively eliminates residual solvents during film formation, ensuring well-defined interfaces between the layers in the OPV devices. As a result, the VESD OPVs demonstrated enhanced PCE and extended operational lifetimes compared to their SC counterparts. Impedance spectroscopy analysis confirmed that the VESD OPVs possessed significantly higher electron mobility and longer electron lifetimes, indicating reduced charge traps and improved charge dynamics. These results highlight the potential of VESD as a versatile technique for controlling molecular orientation in solution-processable organic semiconductors, enabling the development of highly efficient devices with fewer charge traps without relying on synthetic or epitaxial methods.